A study on the general banking and credit risk grading on short term loans in Dutch Bangla Bank Ltd. - Islam, Iftakharul (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.